Relationship between bank indonesia rate, guaranteed rate, and banking lending rates - Astrika Erlin Nurcahningsih; Suhardiono Suhardiono; Hermanto Siregar; Muhammad Sahirul Alim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Maintaining the stability of the Rupiah is a core objective of Bank Indonesia’s monetary policy, in which the BI reference rate serves as a primary instrument. In parallel, the Deposit Insurance Corporation (LPS) sets the deposit guarantee rate, which influences banks’ funding strategies and deposit-taking behavior. The interaction between these two policy rates is crucial, as it directly shapes the interest rates offered by banks to the public, yet empirical studies on their combined impact in Indonesia remain limited. This study specifically investigates how changes in the BI reference rate and the LPS guarantee rate affect commercial banks’ lending and deposit rates. Using monthly secondary data from Bank Indonesia and LPS spanning January 2015 to December 2023, we apply descriptive statistical analysis and Granger causality testing to capture both correlation and directional influence. The results reveal that both the BI reference rate and the LPS guarantee rate have a statistically significant positive effect on banking interest rates, with the BI reference rate exerting a stronger and more immediate influence, while the LPS guarantee rate demonstrates a lagged effect. These findings provide practical insights for policymakers in synchronizing monetary and deposit insurance policies to enhance financial stability, and contribute to the academic literature by clarifying the dual role of policy rates in shaping banking sector pricing behavior.